Stigma and the Structure of Title IX Compliance. Issue 4 (2017) - Beavers, Jenelle M.; Halabi, Sam F.
Abstract : This article analyzes the relationship between the structure of federal Title IX investigations and the existing evidence addressing the emotional and mental health needs of sexual harassment and sexual assault victims. The article argues that federal requirements for investigating sexual harassment should be restructured so as to address the challenges stigma poses for the realization of Title IX's objectives.